1985
DOI: 10.1007/bf00687001
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord multiple sclerosis lesions in Japanese patients: Schwann cell remyelination occurs in areas that lack glial fibrillary acidic protein (GFAP)

Abstract: To extend earlier observations on Schwann cell remyelination in multiple sclerosis (MS) lesions (Itoyama et al. 1983) we immunostained spinal cord sections from eight Japanese MS patients with antiserum to Po glycoprotein, a major constituent of peripheral nervous system (PNS) myelin, myelin basic protein (MBP), and glial fibrillary acidic protein (GFAP). Spinal cord sections from six of the eight Japanese MS patients contained large clusters of peripheral myelin sheaths with anti-Po immunoreactivity. In lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…That study demonstrated that astrocytes expressing AQP4 were more abundant at the periphery of demyelinated plaques as compared with the center of the lesion (Aoki-Yoshino et al 2005). Another important finding in our case of NMO was the relatively preserved MBP-stained myelinated fibers in the lesions, even in the regions near the cavitary lesions where astrogliosis was usually impaired (Itoyama et al 1985). These findings, especially a loss of AQP4 in the lesions, strongly suggest that NMO belongs to a distinct disease entity from MS.…”
Section: Discussionsupporting
confidence: 62%
“…That study demonstrated that astrocytes expressing AQP4 were more abundant at the periphery of demyelinated plaques as compared with the center of the lesion (Aoki-Yoshino et al 2005). Another important finding in our case of NMO was the relatively preserved MBP-stained myelinated fibers in the lesions, even in the regions near the cavitary lesions where astrogliosis was usually impaired (Itoyama et al 1985). These findings, especially a loss of AQP4 in the lesions, strongly suggest that NMO belongs to a distinct disease entity from MS.…”
Section: Discussionsupporting
confidence: 62%
“…This occurs in several experimental animal models of demyelination as well as in human demyelinating disease (Snyder et al 1975;Itoyama et al 1983Itoyama et al , 1985Dusart et al 1992;Felts et al 2005). Schwann cell remyelination occurs preferentially where astrocytes are absent, for example, where they have been killed along with oligodendrocytes by the demyelinating agent (Blakemore 1975;Itoyama et al 1985). Remyelinating Schwann cells within the CNS were generally thought to migrate into the CNS from PNS sources, such as spinal and cranial roots, meningeal fibers, or autonomic nerves following a breach in the glia limitans (Franklin and Blakemore 1993).…”
Section: Demyelinated Cns Axons Can Also Be Remyelinated By Schwann Cmentioning
confidence: 99%
“…Since Schwann cell and oligodendrocyte remyelination in the CNS is a well-known event in demyelinating diseases such as multiple sclerosis (15)(16)(17) as well as in the EB gliotoxic model, the aim of the present investigation was to determine the behavior of these myelin-repairing cells after local EB injection in the brainstem of rats submitted to the diabetogenic model of streptozotocin.…”
Section: Introductionmentioning
confidence: 99%